Molecular Networking Discloses the Chemical Diversity of Flavonoids and Selaginellins in Selaginella convoluta - Reginaldo, Fernanda Priscila Santos; Bueno, Paula Carolina Pires; de, Isabelly CristinaMatos Costa; de, AlanAraújo Roque; Fett-Neto, Arthur Germano; Cavalheiro, Alberto José; Giordani, Raquel Brandt (Planta Medica, 2020)
Selaginella convoluta is a desiccation tolerant plant native to the Brazilian semiarid region (Caatinga), endowed with an effective drought resistance mechanism. As part of our research efforts to understand the chemical diversity of S. convoluta, dehydrated (harvested in their natural habitat in the dry season) and hydrated (plant acclimated in a laboratory after rehydration) specimens were analyzed by HR-LC-ESI-MS/MS followed by a structural annotation on the Global Natural Products Social Molecular Networking Web platform. The molecular networking approach allowed for putative annotation of 39 metabolites, mainly selaginellins and flavonoids. Based on MS/MS data, three unprecedented selaginellins were annotated: 29-hydroxy selaginellin O, 29-hydroxy selaginellin A, and 4-{[2-(4-hydrophenyl)-6-[2-(4-hydroxyphenyl)ethynyl]phenyl](4-oxocyclohexa-2,5-dien-1-ylidene)methyl}benzaldehyde. Th results pointed out that valuable scientific knowledge can be obtained from studies conducted with plants in their natural habitat by allowing a more realistic profile of chemical diversity. The present study adds new information on specialized metabolites of S. convoluta, mainly flavonoids and selaginellins, and highlights the species as an untapped source of chemobiodiversity from Caatinga.
Keywords: Selaginella convoluta; Selaginellaceae; selaginellins; flavonoids; Caatinga